Performance of stage bus service in Keramat corridor / Azian Abd Ghani - Abd Ghani, Azian (1987)
Two important areas were looked into in evaluating the performance of the stage bus service in Keramat Corridor : i. The Past and Present Passenger Performance, and ii. The Present Service Performance. The study was limited.to the corridor-based services (subrarea) to enable a full range of alternatives to be made taking into account to local conditions which enabled detailed coverage of several important aspects of the problems. Three hypoth'Sses were outlined in search of the answer to factors affectinq the decline in the performance of the stage bus service. The spreading of passengers among the many buses due to overlapping of unnecessary services was the answer and a set of new strategies have been suggested to improve the service. Finally, an on-surface discussion on the future prospects of the stage bus service in Keramat Corridor is presented to see the future catchment areas and route coverage networks.